Optimization of the structure of Ha Tinh city’s medium voltage grid by loop cutting algorithm - Dang , Quang Khoa; Tran, Trong Tuan (Journal of Technical Education Science, 2019)
Apply Loop Cutting Methods to cut the closed loop in the medium-voltage grid of Ha Tinh city and select the optimum opening position in the closed power grids opened operation. Change currently loop opening at inappropriate geographic locations. Thereby, adjust the voltage deviation. The results of calculating and selecting the segmentation points on the 22kV loop grid of the Ha Tinh City power electricity using PSS / ADEPT 5.0 software found that the voltage deviation was reduced (power line with large voltage deviation at most 2.5%). The main content of the article is to present the current status of the 22kV roads; presents the steps of calculating closed-loop cutting with PSS / ADEPT software. Thereby assessing the calculation results according to the algorithm and proposing practical applications.